Usefulness of post-bronchoscopic sputum cytology with respect to bronchoalveolar lavage and brush cytology using fiber-optic bronchoscopy in suspected cases of lung cancer - Abhishek Bandyopadhyay,; Mallika Pal,; Saugata Kumar Bhattacharya,; Ruplekha Mitra Mustaphi, (Asian Journal of Medical Sciences, 2022)
Background: Bronchogenic cancer is the most common cause of cancer-related mortality in both sexes all over the world, especially across urban population. However, early diagnosis and timely intervention may minimize the mortality rate to a certain extent and increase the 5-year survival rate to 70–80%. Among the diagnostic modalities available, bronchoscopic biopsy, though gold standard, is less feasible in peripheral centers where we depend more on cytological techniques such as bronchoalveolar lavage (BAL) fluid and sputum cytology for quick diagnosis. Aims and Objectives: This study was conducted at a tertiary care center for studying usefulness of post-bronchoscopic sputum cytology and also to correlate sputum cytology with brushing and washing cytology taking biopsy as the gold standard in the diagnosis of lung cancer. Materials and Methods: A cross-sectional observational study was done in Nil Ratan Sircar Medical College, Kolkata, over a period of 18 months in clinically and radiologically suspected patients of bronchogenic carcinoma. Bronchoscopic samples using a fiber-optic bronchoscope were collected from 50 such patients. In every case, following sequence of events was performed: Pre-biopsy washing (BAL fluid), brushing, biopsy, post-biopsy washing (BAL), and post-bronchoscopy sputum. Cytological examination done and compared with bronchoscopic biopsy specimens of the same. Results: All the available information were meticulously documented in tables and charts along with other variables such as age, sex, morphological types, and cytological and histological diagnosis. SPSS software was used to calculate the efficacy and statistical significance, if any, of these different diagnostic tools and its correlation with the final histological diagnosis. Conclusion: We found that BAL cytology had higher sensitivity and positive predictive value in early and accurate diagnosis of lung malignancy. However, post-bronchoscopy sputum cytology had no additional benefit with respect to BAL and brush cytology (in addition to bronchial biopsy) in diagnosing the same.